Subject authority control in the world of Internet - Micco, Mary (2021)
When we talk about subject authority control today, we must see it as a system that will support searching across the vast domain of the Internet. While we recognize that there are many difficulties, it is time to take a fresh look and to explore new kinds of solutions. Automatically generated graphical displays that identify information objects at many different levels but are organized by broad subject area should be designed as navigation tools. This means we need to take advantage of the new methods of document production by encouraging authors to add in subject keywords and most importantly broad class numbers with the help of expert systems software. This initial cataloging and classification can be refined subsequently by professionals but at least it will form a base for more sophisticated manipulation and indexing from the point of entry into the system. The significant problem today is how to filter out what you dont want and restrict your search to documents likely to be useful.